Protein interactome mining defines melatonin MT1 receptors as integral component of presynaptic protein complexes of neurons. Issue 1 (30th November 2015) - Benleulmi‐Chaachoua, Abla; Chen, Lina; Sokolina, Kate; Wong, Victoria; Jurisica, Igor; Emerit, Michel Boris; Darmon, Michèle; Espin, Almudena; Stagljar, Igor; Tafelmeyer, Petra; Zamponi, Gerald W.; Delagrange, Philippe; et al.
Abstract: In mammals, the hormone melatonin is mainly produced by the pineal gland with nocturnal peak levels. Its peripheral and central actions rely either on its intrinsic antioxidant properties or on binding to melatonin MT1 and MT2 receptors, belonging to the G protein‐coupled receptor (GPCR) super‐family. Melatonin has been reported to be involved in many functions of the central nervous system such as circadian rhythm regulation, neurotransmission, synaptic plasticity, memory, sleep, and also in Alzheimer's disease and depression. However, little is known about the subcellular localization of melatonin receptors and the molecular aspects involved in neuronal functions of melatonin. Identification of protein complexes associated with GPCRs has been shown to be a valid approach to improve our understanding of their function. By combining proteomic and genomic approaches we built an interactome of MT1 and MT2 receptors, which comprises 378 individual proteins. Among the proteins interacting with MT1, but not with MT2, we identified several presynaptic proteins, suggesting a potential role of MT1 in neurotransmission. Presynaptic localization of MT1 receptors in the hypothalamus, striatum, and cortex was confirmed by subcellular fractionation experiments and immunofluorescence microscopy. MT1 physically interacts with the voltage‐gated calcium channel Cav 2.2 and inhibits Cav 2.2‐promoted Ca 2+ entry in an agonist‐independent manner. In conclusion, we show that MT1 is part of the presynaptic protein network and negatively regulates Cav 2.2 activity, providing a first hint for potential synaptic functions of MT1 .